Biogenic metallic nanoparticles as enzyme mimicking agents - Ngcongco, Khanyisile; Krishna, Suresh Babu Naidu; Pillay, Karen (Frontiers in Chemistry, 2023)
The use of biological systems such as plants, bacteria, and fungi for the synthesis of nanomaterials has emerged to fill the gap in the development of sustainable methods that are non-toxic, pollution-free, environmentally friendly, and economical for synthesizing nanomaterials with potential in biomedicine, biotechnology, environmental science, and engineering. Current research focuses on understanding the characteristics of biogenic nanoparticles as these will form the basis for the biosynthesis of nanoparticles with multiple functions due to the physicochemical properties they possess. This review briefly describes the intrinsic enzymatic mimetic activity of biogenic metallic nanoparticles, the cytotoxic effects of nanoparticles due to their physicochemical properties and the use of capping agents, molecules acting as reducing and stability agents and which aid to alleviate toxicity. The review also summarizes recent green synthetic strategies for metallic nanoparticles.